2020
DOI: 10.17085/apm.20043
|View full text |Cite
|
Sign up to set email alerts
|

A novel application of Transnasal Humidified Rapid Insufflation Ventilatory Exchange via the oral route in morbidly obese patient during monitored anesthesia care - A case report -

Abstract: BackgroundTransnasal Humidified Rapid Insufflation Ventilatory Exchange (THRIVE) is used to improve oxygenation, with the added benefit of a smaller increase in CO2 if self-respiration is maintained with THRIVE. Despite these advantages, the use of THRIVE through a nasal cannula is limited in situations such as epistaxis or a basal skull fracture. CaseWe successful used THRIVE, through the oral route under general anesthesia with spontaneous breathing in a morbidly obese patient (weight, 148 kg; height, 183 cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Several studies have reported that pharyngeal catheters deliver oxygen more effectively to alveoli by reducing the distance from the oxygen outlet to the pharyngeal inlet. [9][10][11] A bronchial tube is inserted through the trachea into the bronchus, so that direct delivery of oxygen to the alveoli is possible. An open airway system produces a large amount of leakage, but this can be overcome by using a 70 l/min oxygen flow rate.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that pharyngeal catheters deliver oxygen more effectively to alveoli by reducing the distance from the oxygen outlet to the pharyngeal inlet. [9][10][11] A bronchial tube is inserted through the trachea into the bronchus, so that direct delivery of oxygen to the alveoli is possible. An open airway system produces a large amount of leakage, but this can be overcome by using a 70 l/min oxygen flow rate.…”
Section: Discussionmentioning
confidence: 99%